97.1k views
5 votes
Question number 16 pls answer ​

Question number 16 pls answer ​-example-1
User Bpiec
by
5.2k points

2 Answers

4 votes

Answer:

3(x-2)=4x+1

or, 3x-6=4x+1

or, 3x-4x=1-6

or, -x= -5

or, x=5

Explanation:

step 1. you need to multiply (x-2) by 3

step 2. you need to arrange the equation in proper term which is (3x-4x=1-6)

step 3.after that you need to solve it and answer in both sides will come out in minus (-) which is (-x= -5)

step 4. then the minus (-) on both sides will be canceled and the answer will be 5

3 votes
3x - 6 = 4x + 1
3x - 6 + 6 = 4x + 1 + 6
3x = 4x + 7
3x - 4x = 4x + 7 - 4x

X = -7
:)
User Mufeed
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.